# Pre-Calculus

posted by .

How do you verify:
1.) sinxcosx+sinx^3secx=tanx

2.) (secx+tanx)/(secx-tan)=(secx+tanx)^2

I tried starting from the left on both problems, but am stuck.

like I said before, change everything into sines and cosines.

for the first one:
LS= sinxcosx + (sin^3x)cosx
=(sinxcos^2x + sin^3x)/cosx
=
=
factor out the sinx, and look what you have left inside the bracket!
two more steps!

the second one is just as easy.

LS = (1/cosx + sinx/cosx)(1/cosx - sinx/cosx)
=
=

can you see the common factor, and the difference of squares pattern?

## Similar Questions

1. ### Pre-Calc

Trigonometric Identities Prove: (tanx + secx -1)/(tanx - secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x - 1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1 - cosx)/cosx)/((sinx …
2. ### Simplifying with Trigonometry Identities

Hi, I am a senior in High School having a really difficult time with two problems. I have to prove using the trigonometric identities that they equal each other but I am having a really hard time trying to get them to equal each other. …
3. ### Pre-Calculus

How can this identity be proved/verified?
4. ### Trig

Verify that each of the following is an identity. tan^2x-sin^2x=tan^2xsin^2x I can get it down to cos^2 on the right, but cannot get it to work out on the left. secx/cosx - tanx/cotx=1 On the left I got down to 1-tan^2, but that clearly …
5. ### math

1. (sinx/cscx)+(cosx/secx)=1 2. (1/sinxcosx)-(cosx/sinx)=tanx 3. (1/1+cos s)=csc^2 s-csc s cot s 4. (secx/secx-tanx)=sec^2x+secxtanx 5. (cosx/secx-1)-(cosx/tan^2x)=cot^2x
6. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a negatvie:( …
7. ### Math

Im really struggling with these proving identities problems can somebody please show me how to do these?
8. ### Math

I can't find the integral for (tanx)^(6)*(secx)^(2) I tried splitting up tanx into (tanx)^2*(tanx)^4 and let the latter equal (secx)^2 - 1. Please help, thanks!
9. ### Trig

Verify the identity. (secx + tanx)/(secx - tanx) = (1 + 2sinx + sin(^2)x)/cos(^2)x
10. ### Math

How do i get left side to equal rs? (Tanx/1+secx)+(1+secx/tanx)=(2/sinx)

More Similar Questions